Genetic structure of rainbow trout Oncorhynchus mykiss (Salmoniformes, Salmonidae) from aquaculture by DNA-markers - Bielikova, О. Y.; Mariutsa, A. E.; Mruk, A. I.; Tarasjuk, S. I.; Romanenko, Victoria (My University, 2021)
Th e rational use of valuable fish species from aquaculture is difficult to implement without knowledge of the state of the genetic struc-ture of local stocks. Different types of DNA markers can be used to achieve the goals of selection and breeding work. The genetic structure of a local stock of rainbow trout (Oncorhynchus mykiss Walbaum, 1792) (Salmoniformes, Salmonidae) farmed in Ukraine was studied using DNA-markers: microsatellite (SSR-markers – simple-sequence repeats-markers) and intermicrosatellite (ISSR – inter-simple se-quence repeat). Five fragments of trinucleotide microsatellite motifs with a single anchor nucleotide at the 3'-end were used as a primer for analysis by the ISSR-PCR method. Totally, 85 amplicons were obtained across the five loci, of which 92.9% were polymorphic. The total number of alleles ranged from 10 (marker (ACC)₆G) to 23 (marker (AGC)₆G). The following monomorphic amplicons were determined for the studied local stock of rainbow trout: according to marker (CTC)₆C – 770 and 520 bp bands, for the marker (GAG)₆C – 345, 295 and 260 bp, and for the marker (AGC)₆C – 350 bp. The average number of polymorphic bands per locus was 15.8. The selected ISSR primers had a level of polymorphic information content above the average. The most effective markers for molecular-genetic analysis of rainbow trout were (AGC)₆G and (AGC)₆C according to the percentage of polymorphic bands, marker index, effective multiplex ratio and resolving power. The selected ISSR loci allow the genetic structure of the studied local stock to be characterized using the total and the effective num-ber of alleles per locus (Na and Ne were 1.9 and 1.4, respectively), the Shannon index (average value I was 0.4) and the unbiased expected heterozygosity (mean uHe = 0.3). Microsatellite-based analysis showed features of the genetic structure of the local stock of rainbow trout at six microsatellite loci (OMM 1032, OMM 1077, OMM 1088, Str 15, Str 60, Str 73). Allelic diversity was established and alleles with the highest frequency and most typical for the given stock were identified. The Shannon index and unbiased expected heterozygosity were determined using SSR-markers and were 1.42 and 0.79, respectively. This depicts the complexity of the population structure, a high level of genetic diversity and indicates a high level of heterozygosity of local stock. The “gene pool profile” established as a result of ISSR-PCR in the future will help to differentiate local stocks of rainbow trout in aquaculture of Ukraine. Microsatellite markers provide the ability to de-termine individual features of genetic variation of local populations and to conduct the management of genetic resources on fish farms.
Keywords: fish population genetics; ISSR-PCR; microsatellite marker; genetic polymorphism; population structure; генетика популяцій риб; ISSR-PCR; мікросателітний маркер; генетичний поліморфізм; структура населення; кафедра вищої математики імені проф. Можара В. І.